Nasopalpebral Lipoma sine Coloboma Syndrome—First Case Report - Cheruvu, Ved Prakash Rao; Khan, Manal M.; Arora, Madhuri; Chaudary, Vikas (Indian Journal of Plastic Surgery, 2023)
The nasopalpebral lipoma-coloboma syndrome was described for the first time in 1982. It is an autosomal dominant syndrome with complete penetrance and is characterized by features like congenital symmetric upper eyelid and nasopalpebral lipomas, bilateral symmetric upper and lower eyelid colobomas, broad forehead, widow's peak, abnormal eyebrow pattern, telecanthus, broad nasal bridge, maxillary hypoplasia, and ophthalmological abnormalities. We report a case of a milder variant of the nasopalpebral lipoma-coloboma syndrome that we have termed “nasopalpebral lipoma sine coloboma syndrome.” Such a milder variant is not reported hitherto in the literature. We also describe the surgical correction of the deformity in a case that presented in adulthood, with a satisfactory and pleasing aesthetic outcome.
Keywords: abnormalities; coloboma; lipoma